2017
DOI: 10.18203/2349-2902.isj20170210
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between totally extraperitoneal and transabdominal preperitoneal laparoscopic inguinal hernia repair techniques

Abstract: Background: Laparoscopic groin hernia repair can be done by trans-abdominal pre-peritoneal (TAPP) approach and also by total extra peritoneal (TEP) approach. The objective of this study was to compare the clinical effectiveness and relative efficiency of trans-abdominal pre-peritoneal (TAPP) versus totally extra peritoneal (TEP) techniques of laparoscopic inguinal hernia repair.Methods: All the patients aged 18 years and above admitted in HBT Hospital undergoing laparoscopic inguinal hernia repair were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
0
8
0
3
Order By: Relevance
“…Rhambia et al in 2016 also conducted a comparative study between these techniques; they found that there is no significant difference between them in the variable of duration of surgery, serious adverse event, persisting post-operative pain, hematoma, seroma, persisting numbness, hernia recurrence, port site of hernia and length of hospital stay. TEP gave the patients less pain after 24 hours of surgery in this research [18].…”
Section: Laparoscopic Hernia Repairmentioning
confidence: 53%
“…Rhambia et al in 2016 also conducted a comparative study between these techniques; they found that there is no significant difference between them in the variable of duration of surgery, serious adverse event, persisting post-operative pain, hematoma, seroma, persisting numbness, hernia recurrence, port site of hernia and length of hospital stay. TEP gave the patients less pain after 24 hours of surgery in this research [18].…”
Section: Laparoscopic Hernia Repairmentioning
confidence: 53%
“…The results have been largely non-consistent, with no significant differences between TEP and TAPP. 7,[10][11][12][13] Few studies indicate TEP repair superior to TAPP in terms of postoperative complications, however, learning curve is steeper for TEP, making it a less preferred option as compared to TAPP. [14][15][16] As the era of minimally invasive surgery is advancing, the impact of these techniques on patient's quality of life is necessary to evaluate.…”
Section: Discussionmentioning
confidence: 99%
“…Наличие боли в 1-й послеоперационный день сопровождалось ограничением подвижности, самообслуживания, невозможностью выполнения повседневных дел, выражалось в низкой оценке состояния пациентами своего здоровья в этот период. Болевой синдром у прооперированных методом ТАПП был более значительным, что, возможно, связано с известными особенностями проведения данного типа герниопластики и обусловлено рассечением париетальной брюшины [1,4,6]. Уже к 3-м суткам интенсивность боли снижалась до умеренной и легкой.…”
Section: заключениеunclassified
“…Операции по поводу паховых грыж продолжают оставаться одними из наиболее частых вмешательств в хирургических стационарах. Многие авторы отмечают, что результаты лечения больных паховыми грыжами в последние годы значительно улучшилисьснизилась частота осложнений, уменьшилось количество рецидивов [1][2][3][4][5][6]. Это прежде всего связано с широким внедрением в практику ненатяжных, протезирующих методик пластики пахового канала.…”
unclassified
See 1 more Smart Citation